Anticoagulant Drugs - Božič-Mijovski, Mojca (IntechOpen, 2018)
Anticoagulant drugs are among the most frequently prescribed drugs in everyday clinical practice. In the past decades, several new direct oral anticoagulants were developed that changed the anticoagulant therapy landscape considerably. This book provides an extensive overview of all the known anticoagulants that can be useful for studying different aspects of the haemostatic system or as a starting point for new drug development. It is also a valuable tool for clinicians providing a description of the mode of action and management of therapy for anticoagulant drugs used in everyday clinical practice in different clinical settings, including direct oral anticoagulants dabigatran, rivaroxaban, apixaban and edoxaban.